2014
DOI: 10.1104/pp.114.250340
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Alterations in Primary Metabolism Modulate Susceptibility toTobacco rattle virusin Arabidopsis    

Abstract: During compatible virus infections, plants respond by reprogramming gene expression and metabolite content. While gene expression studies are profuse, our knowledge of the metabolic changes that occur in the presence of the virus is limited. Here, we combine gene expression and metabolite profiling in Arabidopsis (Arabidopsis thaliana) infected with Tobacco rattle virus (TRV) in order to investigate the influence of primary metabolism on virus infection. Our results revealed that primary metabolism is reconfig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
48
0
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 81 publications
5
48
0
15
Order By: Relevance
“…Thus the chlorosis in silenced plants seems not to be related to levels of TRV accumulation. Although TRV makes profound changes in primary metabolism and photosynthesis (Fernandez‐Calvino et al ., ) it did not cause chlorosis when expressed alone. Therefore, although we cannot completely rule out the possibility that chlorosis can be induced by the combined effect of target silencing and TRV, it seems reasonable to assume that down‐regulation of genes identified in this work contributed, at least to some extent, to the development of chlorotic symptoms.…”
Section: Resultsmentioning
confidence: 81%
“…Thus the chlorosis in silenced plants seems not to be related to levels of TRV accumulation. Although TRV makes profound changes in primary metabolism and photosynthesis (Fernandez‐Calvino et al ., ) it did not cause chlorosis when expressed alone. Therefore, although we cannot completely rule out the possibility that chlorosis can be induced by the combined effect of target silencing and TRV, it seems reasonable to assume that down‐regulation of genes identified in this work contributed, at least to some extent, to the development of chlorotic symptoms.…”
Section: Resultsmentioning
confidence: 81%
“…Plant infection by viruses is associated with cellular perturbations, including a massive reprogramming of host gene expression (Hanley‐Bowdoin et al ., ; Lindbo et al ., ; Pallas and García, ; Whitham et al ., ). The analysis of previously published transcriptomic data derived from Arabidopsis tissues infected with viruses (Ascencio‐Ibáñez et al ., ; Babu et al ., ; Espinoza et al ., ; Fernandez‐Calvino et al ., ; Ishihara et al ., ; Marathe et al ., ; Pierce and Rey, ; Rodrigo et al ., ; Yang et al ., ) has indicated that plant colonization is associated with the transcriptional regulation of genes encoding key factors from PTI pathways, such as PRRs themselves, co‐receptors, regulators, MAPKs and transcription factors (Table S1, see Supporting Information). This suggests that cellular components belonging to the PTI machinery may play a role in antiviral defences in plants.…”
Section: Resultsmentioning
confidence: 98%
“…The absence of colour indicates that the corresponding genes are not up‐ or down‐regulated. Data were extracted from transcriptomic analyses published previously (Ascencio‐Ibáñez et al, ; Babu et al, ; Espinoza et al, ; Fernandez‐Calvino et al, ; Ishihara et al, ; Marathe et al, ; Pierce and Rey, ; Rodrigo et al, ; Yang et al, ). ER‐QC, endoplasmic reticulum‐quality control; CDPK, calcium‐dependent protein kinase; MAPK, mitogen‐activated protein kinase; PRR, pattern recognition receptor; RBP, RNA‐binding protein; SERK, somatic embryogenesis receptor kinase (protein family containing BAK1/SERK3 and BKK1/SERK4).…”
mentioning
confidence: 99%
“…TRV was derived from an infectious clone of which pTRV1 was described previously (Liu et al ., ). pTRV2‐GFP contains the soluble modified yellowfish green fluorescence protein (smGFP) coding gene adjacent to the promoter region of the pea early browning virus (PEBV) (Fernandez‐Calvino et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Plants were rub‐inoculated on rosette leaves using fresh inoculum prepared from Nicotiana benthamiana leaves systemically infected with TRV‐GFP as described (Fernandez‐Calvino et al ., ). Arabidopsis control plants were mock‐inoculated with extracts from healthy leaves and processed as the infected plants.…”
Section: Methodsmentioning
confidence: 97%